(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2020)
In this paper, an experimental study has been conducted to show the influence of insertion converge-diverge conical turbulators fitted with rectangular fins inside a circular test tube on Nusselt number, the friction and the overall performance. The air is utilized as working fluid for Reynolds number varied 10000 to 50000. In this investigation, two improvement devices of turbulent heat transfer are utilized. One is the nozzle conical used as turbulators and fixed in the circular tube with three different values of pitch ratio (P.R=1, 1.5 and 2) and the another is rectangular fins placed at the inner surface of the conical turbulators. The conical turbulators fitted with rectangular fins are tested at pitch ratio P.R=1.0 with three different area ratios of the rectangular fins Ar=0.064, 0.106 and 0.149. The experimental results appeared that the heat transfers by using combined the conical nozzle turbulators and the rectangular fins is enhanced by about 234 % for the largest area ratio (Ar =0.149). Also, the optimal thermal performance is obtained to be larger as compared with plain tube case and the conical turbulators alone.